Corporate Social Responsibility and Multinationals in Developing Countries: A Study in Brazil - Barsted, Paula (2006)
Since the rise of the corporation in its modern form in the late nineteenth century, there has been a public concern about the impacts on society associated with the growth of corporate power (Jenkins, 2005). More recently, greater attention is being paid to the role of transnational corporations in developing countries. Globally operating businesses have been called upon to enhance their commitment to the public interest and lead the implementation of corporate social responsible (CSR) practices in developing economies (Raynard and Forstater, 2002; Luetkenhorst, 2004). However, the extent to which multinationals are actually committed to CSR in these countries still remains largely unknown given that most of the empirical studies on CSR have been developed in the context of high income economies (Arora and Puranik, 2004; Belal, 2001; Blowfield and Frynas, 2005). This dissertation contributes to the development of academic research on CSR in developing countries. Besides reviewing the literature related to CSR in developing countries, in Latin America and in Brazil, this study examines to what extent CSR practices differ between large national companies and multinationals in Brazil by scrutinising, using content analysis, social and environmental disclosures in annual reports and corporate websites. The results reveal that multinationals generally present lower levels of CSR adoption in Brazil than large national companies. Through the analysis of the several national and international influences which shape the nature of CSR in this particular country, this study also suggests possible reasons for different levels of CSR adoption between national companies and multinationals. As a way forward, there is the need to perform similar studies in other developing countries in order to examine the extent to which conclusions here obtained can be generalized. Furthermore, given that the empirical study suggests that the potential of multinationals to act as drivers of CSR is far from being fulfilled, there is the need to assess the effectiveness of voluntary agreements currently in place, such as the OECD Guidelines for multinationals and the United Nations Global Compact, as well as test alternative approaches. Finally, this study sheds light on the fact that there is still much to learn about CSR in developing countries and a wide scope for research on this subject, including the actual contributions of CSR to the social and economic development of these economies.